Attaining competitive advantage through market orientation of Public Higher Education Institutions: mediating effect of quality assurance / Zarila Zahari, Rosmimah Mohd Roslin and Carol Teo Boon Chui. - Zahari, Zarila; Mohd Roslin, Rosmimah; Teo, Carol, Boon Chui (Universiti Teknologi MARA Cawangan Selangor, 2016)
The literature review thus far has indicated numerous studies have examined the relationship between market orientation (MO)and competitive advantage (CA)leading to greater organizational performance. A substantial number of studies on strategic management orientations have shown significant relationships between MO and organizational performance but direct contribution of CA is still lacking in consensus. This paper reviews the literature on the influence of market orientation (MO) towards competitive advantage and the mediating effect of quality assurance in public higher education institutions (PHEIs). The reviews specify that market orientation as the marketing strategic platform is likely to achieve superior value in gaining and sustaining competitive advantage however, within the context of PHEIs such relationships are still inconclusive. Quality assurance (QA) is postulated to have a mediating effect in the suggested framework of market orientation and competitive advantage. As QA is becoming a critical factor in the knowledge-based society, this variable needs to be explored further in the context of higher education. Thus, the aim of this paper is to accumulate existing literature in the investigation of the relationship between MO and CA as well as the effect of QA towards the performance of PHEIs based on non-financial dimensions.